Maternal energy-adjusted fatty acid intake during pregnancy and the development of cows' milk allergy in the offspring. Issue 8 (28th October 2022) - Lamminsalo, Anni; Metsälä, Johanna; Takkinen, Hanna-Mari; Tapanainen, Heli; Åkerlund, Mari; Niinistö, Sari; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Knip, Mikael; Kaila, Minna; Virtanen, Suvi M.
Abstract: Cows' milk allergy (CMA) is one of the earliest manifestations of allergic diseases. Early dietary factors, like maternal diet during pregnancy, may play a role in the development of allergic diseases in the offspring. We aimed to investigate the association between maternal intake of fatty acids during pregnancy and the risk of CMA in the offspring. Our study was conducted in a population-based cohort, the Finnish Type 1 Diabetes Prediction and Prevention study. We collected the maternal dietary data by a validated FFQ. We obtained the information on CMA in the study participants ( n 448) from registers and from the parents. Dietary data and information on CMA were available for 4921 children. We used logistic regression in the analyses, and fatty acid intakes were energy adjusted. The maternal intake of SFA, MUFA, PUFA, n -3 PUFA, n -6 PUFA, trans fatty acids, ratio of n -3 PUFA to n -6 PUFA or ratio of linoleic acid to α -linolenic acid was not associated with the risk of CMA in the offspring when adjusted for perinatal factors, background factors, parental history of asthma or allergic rhinitis and infant animal contacts. The intake of α -linolenic acid was associated with a decreased risk (OR 0·72; 95 % CI 0·56, 0·93) of CMA in the offspring of mothers without a history of allergic rhinitis or asthma. In conclusion, the maternal intake of fatty acids during pregnancy is not associated with the risk of CMA in the offspring.